Gustavo Gorriti, Sendero: historia de la guerra milenaria en el Perú (Altre Modernità, 2012)
Gustavo Gorriti, Sendero: historia de la guerra milenaria en el Perú(Lima, 2008, anno, pp. 426. ISBN 978-997-223-946-5)di Elisa Cairati